On the dissection of fibrotic hypodermic connective tissue in aesthetic and plastic surgery - Veronese, Sheila; Rigotti, Gino; Sbarbati, Andrea (Aesthetic Medicine, 2024)
Background: There are many procedures that refer to the dissection of fibrotic connective tissue in the hypodermis: subcision, needle aponeurotomy, percutaneous needle fasciotomy, and Rigottomy. The only aspect that differentiates all these procedures appears to be their therapeutic target. Aim: This systematic review aims to determine whether the aforementioned techniques are different, or if there is redundant terminology, by highlighting differences, similarities, and overlaps between the techniques. Methods: A systematic literature search was conducted using the PubMed database for relevant studies published up to August 2022. Results: Of the 384 articles identified through the literary research, 263 met the eligibility criteria. 46.77% of these came from searching the term "subcision" and referred mainly to aesthetic treatments, such as reducing the visual stigma of scars and improving the appearance of cellulite. 47.53% of the articles referred to the reduction of hand contractures, mainly related to Dupuytren’s disease. The various procedures refer to different applications, but the biological effect they cause are similar. Conclusions: The review provided relevance to the presence of many terms that indicate similar procedures and have similar biological effects, but all refer to fibrotic hypodermic connective tissue dissection. However, the fields of application are different and the clinical results described in the literature suggest the need of an elaborate dialogue between different specialists.